Silen und Theater. Zu Ikonographie und Funktion des betagten Halbtieres in der attischen Vasenmalerei des 5. Jhs. v. Chr - Krumeich, Ralf (Hyperboreus, 2015)
Since around 470/460 BC and obviously under the inﬂuence of contemporary satyr plays, the aged Silen (or Papposilen) appears in many Athenian vase-paintings and provides a new character within Dionysian iconography. From the beginning he is shown as an old satyr with white hair and beard or rather covered all over with white woolly tufts which appear like an artiﬁcial tricot (even if edges are rarely marked clearly). Obviously the ﬁgure of the aged silen – and especially the shaggy variant – reminds of the Papposilen of the satyr play and his theatrical costume (the μαλλωτὸς χιτών). However, several woolly silens are integrated into mythological and ‘family’ contexts since the early Classical period (460/450 BC) which cannot be related directly to theatrical performances. On the other hand, many images of satyr plays show one or more white-haired and -bearded silens without white tufts and thus following an old tradition of showing ‘real’ (younger) satyrs in images of satyr plays. The woolly aged silens depicted within mythological and ‘family’ scenes on Athenian vases of the 5th century BC provide most interesting predecessors of the many Papposilens dressed up with μαλλωτὸς χιτών and cothurnuses which often appear in non-theatrical contexts in South Italian vase-paintings of the late Classical period. Moreover they underline the major importance of theatrical performances seen, received and modiﬁed by creative Athenian vase painters as well as by many recipients of the vases in the 5th century BC.